ANALISIS PERTUMBUHAN EKONOMI, KONSUMSI DAN TABUNGAN DI SUMATERA BARAT - Ningsih, Efrida; Amar, Syamsul; Idris, Idris (Program Studi Magister Ilmu Ekonomi, 2013)
ABSTRACT This article focused on analyze (1) Effect of consumption, investmen, government expenditure and the nett export to the economic growth in West Sumatera. (2) The influence of disposible income, consumption of previous period and the saving on the consumption in West Sumatera (3) Effect of disposible income, interest rate and consumption to the saving in West Sumatera. Data used time series of (I year kuartal 2001 – IV year kuartal 2010). This article use analyzer model equation of simultaneous with method of Two Stage Least Squared (TSLS). Th result of research concludes that (1) the consumption have a significant and positive impact on the economic growth, investment have significant and positive impact on the economic growth, government expenditure have significantly and positive on the economic growth and nett export have a significant and positive impact on the economic growth in West Sumatera. If the economic growth increases, the consumption will also increase. (2) disposible income, economic growth and consumption of previous period significantly influence the consumption in West Sumatera. While the saving is significant and negative effect on consumption in West Sumatera. (3) disposible income and consumption significantly influence the saving in West Sumatera. While the interest rate is not significant effect on saving in West Sumatera. Keywords : Consumtption of Previous Period and Diposible Income